MEDICINAL PROPERTIES OF EDIBLE WEEDS OF CROP FIELDS AND WILD PLANTS EATEN BY ORAON TRIBALS OF LATEHAR DISTRICT, JHARKHAND: Life Sciences-Bio Chemistry - RAPHAEL RANJIT MARANDI; S. JOHN BRITTO (International Journal of Life Science and Pharma Research, 2022)
Latehar district of the state of Jharkhand is inhabited by several tribal groups which constitute 40% of the total population of the district. The Oraons are one of major tribal communities in Latehar dwelling in hills and valleys of the district. They depend on plants or plant products to maintain their livelihood. Ethnobotanical field studies reveal that the Oraons of the district have considerable amount of traditional knowledge of edible weeds from the crop fields and edible wild plants from the forests and hills. During the field study, 101 plant species belonging to 63 genera under 43 families have been recorded which are commonly used by the Oraon community as leafy vegetables. Further study reveals that the edible weeds and the wild plants consist of several medicinal properties.